Polymeric Scaffolds for Regeneration of Central/Peripheral Nerves and Soft Connective Tissues. Issue 3 (29th January 2023) - Cao, Shunze; Bo, Renheng; Zhang, Yihui
Abstract : The advancement in material science and fabrication techniques has led to the booming of tissue engineering in recent years, covering tissue culture, repair, regeneration, and the rest. Among the aforementioned, considering the indispensable roles of central/peripheral nerve and soft connective tissues playing in life‐sustaining activities, their regenerations have attracted intense research attention, especially using polymeric scaffolds, an easy‐to‐access, cost efficient, biocompatible and diverse family of engineering materials. Herein, commonly used natural and synthetic polymeric materials for tissue scaffolds are outlined. Specially, polymer‐based hybrids, being able to provide both structural support and bio‐microenvironments, are discussed. Additionally, representative manufacturing approaches for polymeric scaffolds, including freeze‐drying, electrospinning, 3D printing, soft lithography among others are highlighted. Notably, combined techniques (e.g., electrospinning, 3D printing, etc.) allowing tailorable structural configurations of composite polymeric scaffolds are also reviewed. Furthermore, recent achievements in central/peripheral nerve and soft connective tissues regenerations using polymeric scaffolds are discussed in detail. In the end, conclusions and outlooks are provided to draw a roadmap for future research. Abstract : Polymeric tissue scaffolds stand as promising alternatives for allografts and autografts, owing to their tunable mechanical properties, low cost, broad set of accessible materials, and various fabrication techniques. This review summarizes material selections, fabrication methods, and representative applications of polymeric tissue scaffolds, with a special focus on their crucial role in the regeneration of central/peripheral nerve and soft connective tissues.